2005
DOI: 10.1111/j.1365-2567.2004.02074.x
|View full text |Cite
|
Sign up to set email alerts
|

Follicular dendritic cell dedifferentiation reduces scrapie susceptibility following inoculation via the skin

Abstract: Summary Transmissible spongiform encephalopathies (TSEs) are a group of subacute infectious neurodegenerative diseases that are characterized by the accumulation in affected tissues of PrPSc, an abnormal isoform of the host prion protein (PrPc). Following peripheral exposure, TSE infectivity and PrPSc usually accumulate in lymphoid tissues prior to neuroinvasion. Studies in mice have shown that exposure through scarified skin is an effective means of TSE transmission. Following inoculation via the skin, a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 58 publications
(125 reference statements)
2
49
2
Order By: Relevance
“…In these tissues, PrP RES was observed within likely follicular dendritic cells, cells that have been shown to be important enablers of prion disease propagation and neuroinvasion. 21,[37][38][39][40][41][42][43] Detection of splenic PrP RES at a time point (60 dpi) preceding PrP RES detection in the brain (120 dpi) suggests that splenic-mediated neuroinvasion plays a role in Tg[CerPrP] mice, as has been theorized for scrapie prion transit via nerve fibers associated with follicular dendritic cell-rich splenic germinal centers as conduits to the thoracic spinal cord. 44,45 Although splenic-mediated neuroinvasion remains the most likely possibility, we cannot exclude the possibility of hematogenous neuroinvasion, a phenomenon that, although little investigated, finds support in the literature and in the detection of infectious prions in blood.…”
Section: Discussionmentioning
confidence: 99%
“…In these tissues, PrP RES was observed within likely follicular dendritic cells, cells that have been shown to be important enablers of prion disease propagation and neuroinvasion. 21,[37][38][39][40][41][42][43] Detection of splenic PrP RES at a time point (60 dpi) preceding PrP RES detection in the brain (120 dpi) suggests that splenic-mediated neuroinvasion plays a role in Tg[CerPrP] mice, as has been theorized for scrapie prion transit via nerve fibers associated with follicular dendritic cell-rich splenic germinal centers as conduits to the thoracic spinal cord. 44,45 Although splenic-mediated neuroinvasion remains the most likely possibility, we cannot exclude the possibility of hematogenous neuroinvasion, a phenomenon that, although little investigated, finds support in the literature and in the detection of infectious prions in blood.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is congruent with data from an epidemiological, mathematical, and pathological study, which suggested that for sheep, cattle, and humans, there was an association between development of lymphoid tissues in the gastrointestinal tract and susceptibility to natural TSE infection (40). The precise role that FDCs play in TSE pathogenesis awaits definitive demonstration, but they appear to amplify the levels of the TSE agent above the threshold required to achieve neuroinvasion (11)(12)(13)(14). When and how the TSE agent spreads from the FDCs within PPs to the peripheral nervous system is likewise unknown.…”
Section: Discussionmentioning
confidence: 99%
“…FDCs are a distinct lineage from migratory bone marrow-derived dendritic cells because they are considered to derive from stromal precursor cells, are nonphagocytic, and are nonmigratory (10). In mouse scrapie models, mature FDCs are critical for scrapie agent accumulation in lymphoid tissues, and in their absence, neuroinvasion is significantly impaired (11)(12)(13)(14). From the lymphoid tissues, translocation to the CNS occurs via the peripheral nervous system (15,16).…”
mentioning
confidence: 99%
“…PrP Sc , a protease-resistant isoform of the host protein PrP C , was shown repeatedly to mark the presence of prions and is believed to be the only component of these infectious agents (30,40). Prions invade the nervous system by a mechanism believed to involve mostly transmigration of infected lymphoid cells as well as retrograde transport in ascending peripheral tracts (3,29,35,36,39,41). Once prions enter the brain, replication of infectivity and PrP Sc accumulation occur faster than those in the lymphoid system, subsequently leading to the death of the affected organism (15,20,42).…”
mentioning
confidence: 99%